“Settler Maintenance” and Migrant Domestic Worker Ecologies of Care - Rachel C. Lee; Abraham Encinas; Lesley Thulin (Humanities)
Oral histories of Latina domestic workers in the United States feature hybrid narratives combining accounts of illness and “toxic discourse”. We approach domestic workers’ illnesses and disabilities in a capacious, extra-medical context that registers multiple axes of precarity (economic, racial, and migratory). We are naming this context “settler maintenance”. Riffing on the specific and general valences of “maintenance” (i.e., as a synonym for cleaning work, and as a term for the practices and ideologies involved in a structure’s upkeep), this term has multiple meanings. First, it describes U.S. domestic workers’ often-compulsory use of hazardous chemical agents that promise to remove dirt speedily, yet that imperil domestic workers’ health. The use of these chemicals perpetuates two other, more abstract kinds of settler maintenance: (1) the continuation of socioeconomic hierarchies between immigrant domestic workers and settler employers, and (2) the continuation of (white) settlers’ extractive relationship to the land qua private property. To challenge this logic of settler maintenance, which is predicated on a lack of care for care workers, Latina domestic workers have developed alternative forms of care via lateral networks and political activism.